Interferon-α Is the Primary Plasma Type-I IFN in HIV-1 Infection and Correlates with Immune Activation and Disease Markers - Hardy, Gareth A. D.; Sieg, Scott; Rodriguez, Benigno; Anthony, Donald; Asaad, Robert; Jiang, Wei; Mudd, Joseph; Schacker, Timothy; Funderburg, Nicholas T.; Pilch-Cooper, Heather A.; Debernardo, Robert; Rabin, Ronald L.; et al. (PloS one, 2013)
Type-I interferon (IFN-I) has been increasingly implicated in HIV-1 pathogenesis. Various studies have shown elevated IFN-I and an IFN-I-induced gene and protein expression signature in HIV-1 infection, yet the elevated IFN-I species has not been conclusively identified, its source remains obscure and its role in driving HIV-1 pathogenesis is controversial. We assessed IFN-I species in plasma by ELISAs and bioassay, and we investigated potential sources of IFN-I in blood and lymph node tissue by qRT-PCR. Furthermore, we measured the effect of therapeutic administration of IFNα in HCV-infected subjects to model the effect of IFNα on chronic immune activation. IFN-I bioactivity was significantly increased in plasma of untreated HIV-1-infected subjects relative to uninfected subjects (p = 0.012), and IFNα was the predominant IFN-I subtype correlating with IFN-I bioactivity (r = 0.658, p<0.001). IFNα was not detectable in plasma of subjects receiving anti-retroviral therapy. Elevated expression of IFNα mRNA was limited to lymph node tissue cells, suggesting that peripheral blood leukocytes are not a major source of IFNα in untreated chronic HIV-1 infection. Plasma IFN-I levels correlated inversely with CD4 T cell count (p = 0.003) and positively with levels of plasma HIV-1 RNA and CD38 expression on CD8 T cells (p = 0.009). In hepatitis C virus-infected subjects, treatment with IFN-I and ribavirin increased expression of CD38 on CD8 T cells (p = 0.003). These studies identify IFNα derived from lymph nodes, rather than blood leukocytes, as a possible source of the IFN-I signature that contributes to immune activation in HIV-1 infection.